Equality of opportunity: East vs. West Germany - Andreas Peichl; Martin Ungerer (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The case of German reunification has been subject to extensive research on earnings inequality and labor market integration. however, little is known about the development of equality of opportunity (EOp) in East and West Germany after 1990.Using German micro data, we empirically analyze how circumstances beyond the sphere of individual control explain inequality in East and West Germany. Our results suggest that equal opportunities in Germany have grown since reunification. Interestingly, EOp is larger in East than in West Germany.
Keywords: D63; H2; J62; J7; 330; equality of opportunity; earnings inequality; Germany; family background